Synthesis, Characterization and Biological Evaluation of Some Substituted Thiohydantoins - S, Ramachandran; C.N, Nalini; C.R, Girija; N.S, Begum (Malaysian Journal of Science, 2007)
Thiohydantoins have been proven to have anticonvulsant and antidepressant activity. Some derivatives of thiohydantoin containing both aryl group and benzylidene nucleus were synthesised and their anticonvulsant activity were investigated by pentylenetetrazole induced convulsions. It was found that the activity of Compound C was found to be significant when compared to that of the other three synthesized thiohydantoin compounds. Clonazepam is a marketed potent anticonvulsant drug. Compound C was compared with the clonazepam drug (0.25Âµg/10g).